Theory-based Osteoporosis Prevention Education and Counseling Program for Women: A Randomized Controlled Trial - Aslı Kalkım, RN, PhD; Şafak Dağhan, RN, PhD (Elsevier, 2017)
Purpose: The purpose of this research was to investigate the effect of an osteoporosis prevention program based on the Health Belief Model for women between the ages of 30 years and 45 years at risk of osteoporosis. Methods: This study was conducted with randomized control group pretest, post-test and follow-up trial. Intervention group (n = 37) and control group (n = 36) participated in the research. Data were collected using a sociodemographic data questionnaire, the Osteoporosis Knowledge Test, the Osteoporosis Health Belief Scale, the Osteoporosis Self-efficacy Scale, a monitoring form for estimated dairy calcium intake, and a monitoring form for estimated weekly exercise. Intervention program was composed of a 4-week education program and a 24-week counseling program. Data were collected pretest, post-test 15 days after the end of the education program, follow-up 1 after 3 months, and follow-up 2 after 6 months. Mann Whitney U test, chi-square test, Friedman test, Bonferroni test, two means test and Wilcoxon signed-rank test were used for statistical analysis. Results: After the education and counseling program, a significant increase was seen in comparison with the control group in the mean scores of the intervention group on the Osteoporosis Knowledge Test and its subscales (p < .001), on the Osteoporosis Health Belief Scale and its subscales (p < .001), on the Osteoporosis Self-efficacy Scale and its subscales (p < .001), and in their daily calcium intake (p < .001) and duration of weekly exercise (p < .001). Conclusion: The results of this study were evidence that showed the effects of Health Belief Model-based osteoporosis prevention education and counseling program conducted by nurses.